Reliability and validity of lower extremity and trunk kinematics measured with markerless motion capture during sports-related and functional tasks: a systematic review - Yoma, M.; Llurda-Almuzara, L.; Herrington, L.; Jones, R. (Journal of Sports Sciences, 2025)
This study reviewed the literature regarding reliability and validity of markerless motion capture (MMC) for measuring lower extremities and trunk kinematics during sports-related and functional tasks. Articles published until 28 February 2024 were assessed. Studies were included if they assessed walking, squatting, jumping/landing, running, or cutting. After screening, 53 studies were included in the review. Variability across task characteristics, MMC systems, and statistical analyses was observed. The relative reliability of MMC, measured by intraclass correlation coefficient (ICC), ranged from low to excellent, with most variables showing standard error of measurement (SEM) values below 5°. Squats and landing tasks reported the highest reliability, with good to excellent ICC and most joints reporting SEM values < 5°, except for hip flexion (4.0°to 11.1°). Validity studies (compared to marker-based motion capture) showed differences between technologies ranging from 0.2° to 28.6° and correlations negligible (including negative values) to very strong, depending on the task, plane of motion, and joints analysed. Hip angle in frontal plane reported the lowest differences between technologies across tasks. MMC systems provide reliable measurements for most kinematic variables but are not largely comparable to marker-based systems. MMC reliability creates opportunities to develop more ecological valid research outside traditional biomechanical laboratory settings.